Africa's Competitiveness in the Global Economy (AIB Sub-Saharan Africa (SSA) Series,, 2018)
'This book is a timely effort to rethink Africa's economic narrative. For nearly two decades Africa's popular storyline was represented by the "Africa Rising" meme built on the commodity boom and rise of China as Africa's leading trading partner. It was simple, catchy and hopeful...but optimism alone does not constitute a strategy to guide Africa's search for alternative routes to development. This book provides new intellectual and pragmatic approaches that could help the continent enhance its global competitiveness, a welcome departure from 20th century market liberalisation ideology that defined globalisation as we know it today.' -Calestous Juma, Professor of the Practice of International Development, Harvard Kennedy School, Cambridge, USA This book highlights the key issues, opportunities and challenges facing African firms, industries, cities and nations in their quest to compete successfully in the global economy. Exploring a topic which has grown in importance as Africa faces a period of subdued economic development, this edited collection takes a unique multi-disciplinary, multi-industry and multi-country approach. The authors provide insights into a broad range of issues, including competitiveness measurement and evaluation, sectoral competitiveness of declining and emerging industries, threats of the 'Dutch Disease,' and talent competitiveness. This timely book offers a response to the urgent need for the diversification of economies and the advancement of manufacturing in Africa, appealing to scholars of international business and economics.